What we owe to women: how the governance of Muslim marriage in South Africa impacts Muslim women - Dorasamy, Cassandra (My University, 2021)
State recognition of Muslim marriages in South Africa is an issue that has been debated extensively for many years. Whilst the debate continues, this research documents the experiences of Muslim women who are engaged in legal disputes concerning Muslim Personal Law (MPL) and the experiences of practitioners who work on such matters. The research unpacks three topics emanating from their narratives: representation and power in the public participation process for the Muslim Marriages Bill, the innovative and sometimes blended strategies of practitioners working on MPL related matters, and the individual experiences of Muslim women personally engaged in MPL disputes. The research shows how Muslim women in unrecognised marriages have fallen between two systems of law- the religious and the civil- resulting in them being unable to access their Islamic rights and their constitutionally based rights. Within the context of gender inequality, socio-economic inequality, and limited state capacity to support access to justice and enforce the law, this research raises questions about the efficacy of the law to ensure justice for Muslim women through state recognition. It points to the need for organising beyond the law to ensure gender justice in the civil legal system and gender-just applications of Islamic law in the religious system.
A research report is submitted in partial fulfilment of the Master of Arts in Development Studies to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021